"Virtual Fictional/Factual Positioning": Mediating dialogical concepts in psychological and literary studies. (December 2014) - Barani, Forough; Wan Yahya, Wan Roselezam; Bin Talif, Rosli
At the intersection of psychological and literary studies and acknowledging dialogical aspects of the self in Herman's Dialogical Self Theory (DST), we coined the concept of "Virtual Fictional/Factual Positioning" (VFP), which is also guided by Bakhtin's discussion on the author-hero relation. VFP evaluates the possible dialogical coalition of the author's positions as "I-as-artist/novelist" and "I-as-the-hero-of-my-story, " amongst other positions in literary narratives. Evaluation of the existing literature on DST and the few adaptations of this theory for literary purposes highlights the insufficient consideration paid to the dialogical possibilities of the self in literary studies. To develop our argument based on our new model, we present a textual analysis of Paul Auster's Man in the Dark and examine the protagonist's narratives and his relation with his hero in the story within the story. Furthermore, we address the question of whether this protagonist/author's self consists of polyphonized dialogical voices or merely a cacophony of various thoughts with fewer logical and no dialogical qualities.